Face validity of a virtual reality simulation platform to improve competency in endoscopy: a prospective observational cohort study - Eley, Catherine; Hawkes, Neil D; Egan, Richard J; Robinson, David B; Brown, Chris; Murray, Sam; Siau, Keith; Lewis, Wyn (Endoscopy International Open, 2022)
Background and study aims Virtual reality endoscopic simulation training has the potential to expedite competency development in novice trainees. However, simulation platforms must be realistic and confer face validity. This study aimed to determine the face validity of high-fidelity virtual reality simulation (EndoSim, Surgical Science, Gothenburg), and establish benchmark metrics to guide the development of a Simulation Pathway to Improve Competency in Endoscopy (SPICE). Methods A pilot cohort of four experts rated simulated exercises (Likert scale score 1–5) and following iterative development, 10 experts completed 13 simulator-based endoscopy exercises amounting to 859 total metric values. Results Expert metric performance demonstrated equivalence (P = 0.992). In contrast, face validity of each exercise varied among experts (median 4 (interquartile range [IQR] 3–5), P < 0.003) with Mucosal Examination receiving the highest scores (median 5 [IQR 4.5–5], P = 1.000) and Loop Management and Intubation exercises receiving the lowest scores (median 3 [IQR 1–3], P < 0.001, P = 0.004), respectively. The provisional validated SPICE comprised 13 exercises with pass marks and allowance buffers defined by median and IQR expert performance.Conclusions EndoSim Face Validity was very good related to early scope handling skills, but more advanced competencies and translation of acquired clinical skills require further research within an established training program. The existing training deficit with superadded adverse effects of the COVID pandemic make this initiative an urgent priority.